Birth of Two Pan Pioneers - Anthony, Michael (Express)
This article examines the birth of two pan pioneers, Ellie Mannette and Winston "Spree" Simon.
Keywords: Arrangers (Musicians) -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago -- History; Musicians -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago